A Study on The Buying Behavior of Consumers Toward Cosmetic Products in Large Retail Outlets with Special Reference to Chennai City - Shamsudin, Mohd Farid; Basha, Mohamed Bilal; Saida, Kausar; Kadir, Baharudin (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this paper is to study the consumer buying behavior towards cosmetic products in large retail outlets in the Chennai region, Tamilnadu. The paper focused on impact of the service variables like store design factors, store ambience factors, sales personnel factors, products related factors, promotional factors, convenience factors, celebrity endorsement and advertisement effect on the purchase behavior of consumers. The study used survey methodology to collect data from the respondents who were consumers of cosmetic products. The sample size of the study was 384. The data collected was analyzed using SPSS 20.0 software. Research hypotheses were framed and the statistical tests like independent sample t- test, one-way ANOVA and regression analysis was conducted to test the hypothesis. It was found that store related factors like design, ambience, convenience, variety, promotional effort, quality of service was most commonly influencing the purchase behavior of consumers